TINGKAT INFESTASI CACING HATI PADA KAMBING DI KELOMPOK TERNAK KECAMATAN SUKOHARJO KABUPATEN PRINGSEWU PROVINSI LAMPUNG - Siti Tika Fatmawati; Siswanto Siswanto; Purnama Edy Santosa; Arif Qisthon; Johan Arfianto (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2022)
Research on liver worm infestation levels in goats was held on 1--30 March 2021 at three livestock groups of Rukun Amrih Sentosa, Mekar 4, and Sido Makmur in Sukoharjo District, Pringsewu Regency. This research aimed to know the infestation level of liver worms in goats. The research method was a survey method with proportional random sampling. The number of samples was 85 goats from the livestock group in Sukoharjo District. Examination of fecal samples was carried out at the Parasitology Laboratory Lampung Veterinary Center using a sedimentation test. The data obtained were presented in tabulation form and then analyzed descriptively. The results showed that the liver fluke infestation level on goats was found at Rukun Amrih Sentosa at 3.77%, while at Mekar 4 and Sido Makmur, the liver fluke infestation was not found (0%). From the results of the examination of samples in Sukoharjo District, it was known that there were 2 positive samples of Fasciola (2.35%) from 85 samples examined, meaning that the level of liver worm infestation in the livestock group of Sukoharjo District was low. Keywords: Goat, Infestation level, Liver worms